Rancang Ulang Portal Otomatis Berbasis Mikrokontroler ESP32 Menggunakan Sensor Ultrasonik HC-SR04 - Koto , Indra; Sahabuddin Nasution, Muhammad Edy; Gulo , Yanuardi; Derisman , Aken (SURYA TEKNIKA, 2026)
An automatic barrier gate system is a crucial component for efficient and secure vehicle access management. A device previously developed by other researchers had become inoperable due to a faulty ultrasonic sensor and relied on only a single sensor for vehicle detection. This study aimed to redesign the automatic gate system by replacing the defective component and increasing the sensor count to two HC-SR04 ultrasonic sensors: one at the front to trigger the barrier to open and one at the rear to trigger it to close. An ESP32 microcontroller serves as the main controller, reading distance data from both sensors and sending commands to a servo motor that actuates the barrier arm. The study employed the Research and Development (R&D) method, comprising the stages of requirements analysis, design, implementation, and testing. Test results demonstrated that the system functions normally, with sensor response times ranging from 0.20 to 0.27 seconds within a detection range of 0.05–0.3 meters, and achieved a 90% success rate. The system operates correctly: the automatic barrier opens when a vehicle is detected by the opening sensor at a specific distance and closes after the vehicle is detected passing the closing sensor. This redesign successfully resolved the issues with the previous device and enhanced the reliability of the vehicle detection system through the use of dual ultrasonic sensors.